LIFE CYCLE ASSESSMENT (LCA) SEBAGAI METODE KAJIAN DAMPAK LINGKUNGAN PROSES PENGOLAHAN AIR BERSIH DI INSTALASI PENGOLAHAN AIR (IPA) SIWALANPANJI - Tuhu Agung Rachmanto; Aulia Ulfah Farahdiba; Geafiata Amalia Nurbaiti (EnviroUS, 2022)
The Siwalanpanji Water Treatment Plant with conventional and non-conventional processing has an impact on the environment due to the water treatment process. This study aims to identify potential impacts on the environment, analyze factors causing environmental impacts that arise, and provide recommendations for environmental impact management as an alternative plan for appropriate and environmentally friendly improvements using Life Cycle Assessment (LCA) which will be analyzed through Simapro software. LCA is an approach method used to identify and analyze environmental impacts resulting from all stages of the product life cycle so that it will be known which parts have the greatest impact on the environment. The three highest impacts that arise from the Impact 2002+ method are Respiratory inorganics, Global Warming, and Non-Renewable Energy. Factors causing these impacts come from the use of electricity and the provision of chemicals in the form of coagulants and disinfectants. Alternative improvements that can be given to reduce the impact that occurs include increasing equipment efficiency and substitution of Poly Aluminum Chloride coagulant with Aluminum Sulfate.